EVALUATION OF WEIGHT REDUCTION EFFICACY AND SAFETY OF SIBUTRAMIN-CONTAINING DRUGS IN PATIENTS WITH ALIMENTARY OBESITY - T. Yu. Demidova; M. Ya. Izmailova; S. E. Ushakova; K. Ya. Zaslavskaya; A. A. Odegova; V. V. Popova; M. E. Nevretdinova; P. A. Bely (Фармация и фармакология (Пятигорск))
The article presents clinical study results of the efficacy and safety of combination therapy with sibutramine and metformin (fixed combination) in comparison with sibutramine therapy with microcrystalline cellulose in patients with alimentary obesity.The aim is to evaluate the efficacy and safety of using the sibutramine+metformin fixed dose combination (Reduxin® Forte) and compare it with the sibutramine + microcrystalline cellulose combination (Reduxin®) in patients with alimentary obesity in the course of the obesity therapy.Materials and methods. Male and female patients (240 people) aged 18 to 65 years inclusive with alimentary obesity, meeting the inclusion criteria and not meeting the non-inclusion criteria, were randomized into 2 groups in a 1:1 ratio. One group (n=120) received sibutramine+ metformin p. o., 1 tablet (850 mg + 10 mg) once per day, the second group (n=120) received sibutramine+ microcrystalline cellulose (MCC) p. o., 1 capsule (10 mg + 158.5 mg) once per day in the morning. On day 30 ± 1, in the absence of a 2 kg weight loss compared to the first visit, the dose was increased in accordance with the medical instruction. The therapy period was 180 days. The randomization list was generated by the factory method of random numbers. The efficacy and safety were assessed by anthropometric, clinical and laboratory parameters and the SF-36 questionnaire. The proportion of patients who achieved a decrease in body weight by more than 5% in 6 months, the magnitude and dynamics of changes in body weight and body mass index, waist and hip measurements, their ratios, changes in lipid profile, blood pressure, as well as the total number of adverse events, their frequency and nature of occurrence were analyzed.Results. The both drugs have demonstrated efficacy in all parameters of the obesity therapy. At the same time, in a comparative analysis, a statistically significant advantage of therapy with sibutramine + metformin was demonstrated in relation to the proportion of patients who had achieved more than 5% weight loss (body weight dynamics). Significant benefits were shown in terms of the magnitude of the change in body mass index (BMI); there was a statistically significant increase in the proportion of the patients who had switched from one category of BMI to another. By the end of the study, the vast majority of patients had no longer met the criteria for the diagnosis of “Obesity”. There was also a statistically significant benefit of sibutramine + metformin in terms of lowering triglycerides and low-density lipoprotein levels. The analysis of the safety parameters of sibutramine + metformin confirms a high safety profile of the drug, a comparative statistical analysis of adverse events in terms of their presence, severity, causal relationship with therapy and outcome have not revealed intergroup differences. Adverse events were transient and did not require discontinuation of therapy.Conclusion. The results of the study showed that therapy with Reduxin® and Reduxin® Forte provides a pronounced decrease in body weight. However, the use of a fixed combination has a more effective positive effect on the lipid profile and patients’ quality of life, which, combined with a high safety profile, proves the possibility and expediency of using Reduxin® Forte for the treatment of obesity and restoring metabolic health, even in patients without additional carbohydrate metabolism disorders.